Konsumsi Rokok Berdasarkan Karakteristik Individu di Indonesia - Sugiharti, Lilik; Sukartini, Ni Made; Handriana, Tanti (Jurnal Ekonomi Kuantitatif Terapan; 2015: Vol. 8, No. 1, Februari 2015 (pp. 1-112), 2015)
This study analyzes the correlation of smoking behavior and general health status of respondents and explores individual characteristics as determinant of individual becoming a smoker in Indonesia. This study utilizes data from Indonesia Family Life Survey (IFLS) on 2000 and 2007. Correlation analyzes and probit regression are the main estimation strategy in this study. There is negative correlation between smoking behavior and general health status of respondents. This finding implies that smokers tend to report their general health status are not good. From the probit regression for IFLS data in 2000 and 2007, it is found there is inverse relationship between smoking behavior and educational level. This imply that individual with primary educational level tend to be smoker with higher probability than individual with higher educational level. Corresponding with income level and housing status, this study finds that smoking behavior in Indonesia related with individual with lower income level.
Keywords: cigarette consumption behaviour; individual characteristics; IFLS